A Toolkit for Measuring Early Childhood Development in Low and Middle-Income Countries - Fernald, Lia C. H.; Prado, Elizabeth; Kariger, Patricia; Raikes, Abbie (World Bank, Washington, DC, 2017)
The Toolkit provides a practical, “how-to” guide for selection and adaptation of child development measurements for use in low- and middle-income countries. Users can follow the proposed step-by-step process to select, adapt, implement, and analyze early childhood development data for diverse purposes and projects. Researchers, evaluators, and program personnel from various disciplines interested in assessing early childhood development in low- and middle-income countries will find the book useful for planning and evaluating interventions, monitoring development over time, or conducting a situation analysis. The book updates and expands a previous 2009 edition, incorporating new research on the use of child development measurement tools in low- and middle-income countries. The ECD Measurement Inventory that accompanies this Toolkit contains 147 measurement tools for children under 8 years. For each test it reports the domains assessed, age range for which the tool is appropriate, method of administration, purpose of the assessment, origin and locations of use, logistics, and cost.